2021
DOI: 10.1186/s13039-020-00521-2
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal testing for assessing foetal sex chromosome aneuploidy: a retrospective study of 45,773 cases

Abstract: Objective To assess the positive predictive value (PPV) of noninvasive prenatal testing (NIPT) as a screening test for sex chromosome aneuploidy (SCA) with different maternal characteristics and prenatal decisions in positive cases. Materials and methods We retrospectively analysed 45,773 singleton pregnancies with different characteristics that were subjected to NIPT in the Maternity and Child Health Hospital of Anhui Province. The results were va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…A unique aspect of prenatal genetic counseling following an NIPT result positive for SCA is the presentation, interpretation and often calculation of the positive predictive value (PPV). The PPV for NIPT results regarding SCAs is inherently variable among laboratories with published values ranging from 20-86% (Lu et al, 2021; Petersen et al, 2017; Ramdaney et al, 2018; Shi et al, 2021). A 2019 review of 10 NIPT laboratory reporting methods concluded recommendations that laboratory reports visibly and clearly state the detection rate (DR), specificity (SPEC), positive predictive value (PPV), and negative predictive value (NPV) for all conditions being screened in order to assist patients and providers in making decisions and interpreting results (Skotko et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A unique aspect of prenatal genetic counseling following an NIPT result positive for SCA is the presentation, interpretation and often calculation of the positive predictive value (PPV). The PPV for NIPT results regarding SCAs is inherently variable among laboratories with published values ranging from 20-86% (Lu et al, 2021; Petersen et al, 2017; Ramdaney et al, 2018; Shi et al, 2021). A 2019 review of 10 NIPT laboratory reporting methods concluded recommendations that laboratory reports visibly and clearly state the detection rate (DR), specificity (SPEC), positive predictive value (PPV), and negative predictive value (NPV) for all conditions being screened in order to assist patients and providers in making decisions and interpreting results (Skotko et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal genetic counseling for SCA-positive NIPT results is challenged by relatively poor positive predictive values for SCAs in NIPT, highly variable phenotypic outcomes, and historic peer-reviewed publications inherently biased by ascertainment (Mennuti, Chandrasekaran, Khalek, & Dugoff, 2015; Petersen et al, 2017; Wang et al, 2020). While NIPT has been demonstrated to have high sensitivity and specificity in identification of other chromosomal conditions, such as Trisomy 21/Down syndrome, the positive predictive values (PPV) for the detection of SCAs have varied from 25-89% and many companies fail to include these test statistics for SCAs on their result reports entirely (Lu et al, 2021; Shi et al, 2021; Skotko et al, 2019; Zheng et al, 2020). Phenotypes among SCAs range widely from mild dysmorphisms and tall stature to increased rates of cognitive impairment, medical conditions and psychological features.…”
Section: Introductionmentioning
confidence: 99%
“…A Welsh survey of pregnancies with Turner syndrome found a termination rate of 66% over 10 years. A Chinese study of sex chromosome aneuploidies detected through NIPT screening reported termination rates of 85%, 73%, 20%, and 10% for Turner syndrome, Klinefelter syndrome, XXX, and XYY, respectively [46]. In a study from Hong Kong, the overall termination rate for sex chromsome aneuploidies was 55.6%, with specific rates of 91.7%, 48.0%, 23.4%, and 4.8%, for 45,X, 47,XXY, 47,XXX, 47,XYY, respectively [47].…”
Section: Preventing Genetic Disease: a Public Health Perspectivementioning
confidence: 99%
“…Sex chromosome aneuploidies that can also be identified using NIPT have a lower detection rate, especially monosomy X, with a higher false positive rate compared to autosomal trisomies. The average positive predictive value (PPV) for sex chromosome anomalies screening was estimated at 40.56% [5,11]. NIPT has several limitations regarding the detection of more rare fetal chromosomal abnormalities, other than aneuploidy for 3 (13,18,21) or 6 pairs (13,18,21,9,16,22) of autosomal chromosomes, or the identification of cases with mosaicism.…”
Section: Introductionmentioning
confidence: 99%